The Taxing Dynamic: Corporate Income Tax Rates and Macroeconomics Indicators’ Impact on Foreign Direct Investment in ASEAN - Ine Ratna Dewi; Masruri Mochtar; Pardomuan Robinson Sihombing (Jurnal Akuntansi dan Perpajakan, 2023)
Foreign investment as alternative funding in accelerating economic growth and development increases the climate of competition between countries in attracting investment flows. This study aims to determine the effect of corporate income tax rates and macroeconomic indicators on foreign direct investment (FDI) inflows to ASEAN member countries during the period 2013 to 2019. Using data sourced from publications of The World Bank, OECD, and KPMG, this paper used the panel data regression method. Using the Random Effects Model, this study shows that there is no statistically significant relationship between corporate income tax rates and FDI inflows in ASEAN member countries. Variables that have a significant influence on FDI inflows are macroeconomic indicators in the form of the market size (GDP), trade openness, and inflation rate. So that the results of this study can be used as a consideration in policy making in ASEAN, especially in increasing domestic investment inflows.